Hydrocarbon production and biodiesel properties of a green microalga Botryococcus braunii KMITL 2 cultivated outdoor in open pond and closed photobioreactor - Ruangsomboon, Suneerat (My University, 2018)
Botryococcus braunii is a promising feedstock for biodiesel production. In general, selection of the most suitable cultivation systems is based on profitable yield and oil quality. The feasibility of using this alga as feedstock for commercial biodiesel production was tested by comparing the cultivation in open pond and closed photobioreactor under the 5 g⋅kg-1 optimum salinity condition previously found, and the results were that the hydrocarbon content (40.7±1.6%) of the alga cultivated in open pond was higher than that cultivated in the photobioreactor and its biomass (2.9±0.1 g⋅L-1) was much higher; its biodiesel properties, however, were nearly identical with cetane values of 48.15-56.99. Drastically different though were the hydrocarbon yields-cultivation in the open pond produced 2.3 times higher yield than the closed photobioreactor. Hence, outdoor cultivation under optimum salinity in open pond was considered suitable for biodiesel production by this algal strain.
Keywords: Carbohydrate; Carotenoid; Cetane; Chlorophyll; Fatty acid; Protein